Pengaruh External Pressure, Financial Target, Ineffective Monitoring dan Rationalization terhadap Financial Statement Fraud pada Industri Food And Beverages yang Terdaftar di BEI Tahun 2020-2022 - Dede Pramurza (AKUNTANSI 45, 2024)
The analytical method used is a quantitative descriptive analysis method using statistical analysis. The data source in this research comes from annual financial reports. Data collection techniques in this research were carried out in 2 ways, namely: library research techniques and field research techniques. The research results show that External Pressure, Financial Target, Infective Monitoring, and Rationalization have no effect on Financial Statement Fraud in the Food and Beverages industry listed on the IDX in 2020-2022 either partially or simultaneously and the magnitude of the influence is 4.6% Keywords:,,,